Market chain analysis of red pepper: The case of Bure Woreda, West Gojjam Zone, Amhara National Regional State, Ethiopia - Abay, A. (Haramaya University, 2010)
In Bure, West Gojjam zone, Amhara region red pepper is a major cash crop which is mainly produced by smallholder farmers. The basic objective of this study was to analyze profitability of red pepper production, determinants of household’s marketable surplus and the degree of market integration in major regional intermediate markets using primary data collected from households through semi structured questionnaire. The producers’ survey result revealed that all farmers supply the product to the market and 85.3% of red pepper produced by the sampled farmers in the production year was supplied to the market. Farmers in the Woreda do not have any standard measure to identify the quality of pepper. They usually identify quality of red pepper by its color, pest damage, size, shape, odor and foreign matter. In the Woreda, the four largest traders handled 30.2% of the total volume of purchased pepper. Hence the structure of the pepper market in the study area was some what competitive. The profitability analysis also indicates that red pepper production was profitable. The average amount of red pepper supplied to the market by producers was 5.24 quintal with minimum amount of 0.5 quintals and maximum of 19 quintals. The variables that influenced the marketable supply positively were agricultural experience, access to credit, yield, land size, current year and lagged prices. Among the significant variables yield and access to credit were highly significant at less than 1% significant level. The result of market integration analysis also shows that pepper markets in the western part of the region were integrated. The major problems identified are low access to improved inputs, collateral problem to get credit, poor storage facilities and low price of produce. To solve these problems increased access to improved inputs, strengthening credit institutions, strengthening of cooperatives, education and training, price information and establishment of storage and processing facilities are recommended.